Surgical pearl on reconstructing surgical defects of the nasal tip (Dermatology Reports, 2016)
Repairing surgical defects of the nasal tip is challenging, mainly because of the lack of freely mobile skin available peripherally. The Peng flap is a one-stage cutaneous flap that circumvents this difficulty by recruiting skin from the nasal dorsum and sidewall regions. The design produces a tridimensional shape perfectly adapted to the configuration of the nasal tip and allows for an inconspicuous closure of the defect. We present three examples of full-thickness skin defects involving the nasal tip, reconstructed using a modified version of the Peng flap, and present the experience at our department with this surgical technique.